Building Tolerance and Religious Harmony in Indonesia through Religious Moderation - Agustin Suci Rizkianti; Siti Ropiah; Ika Kartika; Rudi Iskandar (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to analyze the concepts and principles of religious moderation, examine its role in fostering tolerance and interreligious harmony, and identify the challenges and opportunities in implementing religious moderation within Indonesia’s multicultural society. Religious moderation is viewed as a strategic approach to maintaining social harmony amid the country’s religious, cultural, and ideological diversity. The research employs a qualitative approach using a library research method. Data were collected through a critical review and analysis of scholarly literature, including peer-reviewed national journals published after 2022, academic books, and relevant policy documents related to religious moderation. Data analysis was conducted through data reduction, thematic categorization, and descriptive-analytical interpretation to achieve a comprehensive understanding of the research focus. The findings indicate that religious moderation plays a crucial role in strengthening tolerance and interreligious harmony in Indonesia by promoting balance, justice, inclusivity, and respect for diversity. The study reveals that religious moderation is effectively implemented through education, interfaith dialogue, the involvement of religious leaders, and supportive public policies that encourage harmonious religious life. However, its implementation continues to face several challenges, such as exclusive religious interpretations, the spread of extremism in the digital era, uneven public understanding of religious moderation, and the politicization of religion. On the other hand, significant opportunities exist, including strong governmental support, the integration of religious moderation into educational curricula, the use of digital media to disseminate moderate values, and the development of community-based religious moderation initiatives. In conclusion, religious moderation is an essential and relevant approach for maintaining tolerance and interreligious harmony in Indonesia. The success of its implementation depends largely on the synergy between government institutions, educational establishments, religious leaders, and civil society. The implications of this study emphasize the importance of strengthening policies, education, and socio-religious literacy based on religious moderation in a sustainable manner to ensure that the values of tolerance and harmony become deeply embedded in Indonesian society.